Intention to adopt industry 4.0 technologies among dairy manufacturers in Malaysia - Wahab, Saeedi Sayed Abdul (2019)
Small and medium enterprises (SMEs) are one of key economic growth engines which play vital roles in Malaysia’s economy. In the manufacturing sector, SMEs are considered as the backbone of industrial development. Presently, dairy manufacturing industry is one with high potentials; thus, ensuring production of quality of dairy products is indispensable. Technology is one of the enablers that can assist companies improve their performances. Consequently, high-technology companies achieve immense competitive edge over their rivals. Improved product quality, sustained higher productivity, reduced output errors, and improved income are among the benefits of using technology. Recent studies have reported that Malaysia’s SMEs are often faced with some challenges and the studies have listed low productivity, shortages of managerial capabilities, financial problems including access to credit facilities, and low intention of technology adoption as some of the ever existing problems. Among these challenges, the studies revealed that intention towards technology adoption is most crucial. Presently, SMEs are still hesitant to embrace and adopt new technology. In attempts to fill up these gaps, the present study was undertaken with the main purpose of determining the level of intention to adopt Industry 4.0 Technologies among SMEs focusing on Malaysia’s dairy manufacturing industry. The study adopted both Theory of Planned Behaviour (TPB) and Technology Acceptance Model (TAM) to address the confronting issues. The two theories consisted of six constructs in which constructs perceived usefulness (PU), perceived ease of use (PEU), subjective norms (SN), and perceived behavior control (PBC) were assumed as the independent variables. Construct Attitude (Att) to adopt Industry 4.0 Technologies was the presumed mediating variable, while Intention (Int.) to adopt same was the dependent variable. A total of 156 sets of questionnaires were made available to owners and managers of respective registered SMEs using email addresses and face to face interviews via structural questionnaire, out of which, 114 sets responded successfully. Partial Least Square-Structural Equation Modeling (PLS - SEM) was used as a statistical tool to analyze collected data. The findings revealed that intention of SMEs to adopt Industry 4.0 Technologies was positively influenced by PU, PEU, PBC and Att. In addition to direct effects of the constructs, the study also indicated mediating effect of Att. on the relationships between PU, PEU and Int. to adopt technologies. The study disclosed that Att, mediated both the relationships between PU, PEU and Int. to adopt Industry 4.0 Technologies. The findings supported the assumptions of TPB although it was confined to a sampling frame of 114 out of 156 SMEs (73.08 percent) which could impose limitation in generalization on the adoption of Industry 4.0 Technologies. Hence, for future studies, increase in number of respondents must be considered as utmost importance. The findings of the study could assist managers and higher authority in SMEs and policy makers to fully understand the impact of Industry 4.0 Technologies on their manufacturing operations and give an insight to academicians/researchers in applying and or improving the model while accessing other intention of technology adoption in future research. In conclusion, the study has made an effort to determine attitude and intention of entrepreneurs in SMEs to gain competitive benefits over rivals and for their sustainable growth.